Analysis of Place Attachment in Coffee Shop - Novrial; Pasaribu, Rifdah Fadhilah; Affif, Aulia Malik (International Journal of Architecture and Urbanism, 2026)
Place attachment is a state in which an individual feels attached to a place due to repeated positive attractions and interactions. The increasing existence of coffee shops is becoming a new lifestyle trend today. The ability of public spaces to attract the attention of visitors to be comfortable and at home can be seen from the attractiveness factor. The attraction factor consists of two categories, namely places and events. The category of places is described in the attractiveness of design and comfort, while the category of events is described in the activity. The purpose of this study was to determine the place attachments to coffee shops. The research method used is a mixed method with 100 questionnaires to coffee shop visitors and field observations. The research was analyzed using descriptive methods. The result shows that tables and chairs are interior elements that are the attraction of the design, the cozy and intimate atmosphere is a factor in visitor comfort, and the activities that are liked and often done in coffee shops are drinking coffee, socializing/hanging out, and studying/working.